2009
DOI: 10.1038/nsmb.1620
|View full text |Cite
|
Sign up to set email alerts
|

Control of alternative splicing through siRNA-mediated transcriptional gene silencing

Abstract: When targeting promoter regions, small interfering RNAs (siRNAs) trigger a previously proposed pathway known as transcriptional gene silencing by promoting heterochromatin formation. Here we show that siRNAs targeting intronic or exonic sequences close to an alternative exon regulate the splicing of that exon. The effect occurred in hepatoma and HeLa cells with siRNA antisense strands designed to enter the silencing pathway, suggesting hybridization with nascent pre-mRNA. Unexpectedly, in HeLa cells the sense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
319
3
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 311 publications
(345 citation statements)
references
References 45 publications
19
319
3
4
Order By: Relevance
“…The existence of specific nuclear roles for these proteins in mammalian cells was demonstrated at the individual gene level for the mechanism of transcriptional gene silencing either acting at the promoter level (18,34,35) or intragenically in the regulation of alternative splicing (3,10,23). In particular, the fact that AGO1 was shown to interact with chromatin-embedded proteins such as chromatin modifiers, splicing factors (10), and RNA polymerase II (13) prompted us to define the DNA targets of AGO1 at a genomewide level using ChIP-seq in human cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The existence of specific nuclear roles for these proteins in mammalian cells was demonstrated at the individual gene level for the mechanism of transcriptional gene silencing either acting at the promoter level (18,34,35) or intragenically in the regulation of alternative splicing (3,10,23). In particular, the fact that AGO1 was shown to interact with chromatin-embedded proteins such as chromatin modifiers, splicing factors (10), and RNA polymerase II (13) prompted us to define the DNA targets of AGO1 at a genomewide level using ChIP-seq in human cells.…”
Section: Discussionmentioning
confidence: 99%
“…5 B and C). All these features prompted us to investigate whether SYNE2 E107 inclusion is regulated in an AGO1-dependent manner, in particular, through the TGS-AS mechanism (3,23). Because an essential part of the TGS-AS mechanism is inhibition of RNAPII elongation, we first evaluated how SYNE2 E107 responds to activators and inhibitors of elongation.…”
Section: Ago1 Preferentially Associates With Active Enhancers But Doementioning
confidence: 99%
See 2 more Smart Citations
“…Consistently, the transcription-associated H3K36me3 modification is less prominently enriched in alternatively spliced exons than in constitutive exons [8]. In an opposite way, chromatin remodelers such as SWI/SNF [9] or siRNAs that trigger silencing histone marks such as H3K9me2 and H3K27me3 through a argonaute-1-mediated transcriptional gene silencing mechanism [10] were shown to create local chromatin compactions that act as roadblocks to pol II elongation, in turn affecting alternative splicing decisions. Furthermore, several genome-wide studies showed that nucleosomes are preferentially positioned in exons [11,12,13] and this positioning may act as a transient barrier to elongation that helps exon recognition at the RNA level [14,15].…”
mentioning
confidence: 70%